2020
DOI: 10.1186/s12970-019-0324-5
|View full text |Cite|
|
Sign up to set email alerts
|

Correction to: The effect of low dose marine protein hydrolysates on short-term recovery after high intensity performance cycling: a double-blinded crossover study

Abstract: The original article [1] contains errors in Tables 1 and 3: Table 1 erroneously mentions use of a treadmill which should instead state ‘bicycle’, and Table 3 has a minor typesetting mistake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 1 publication
6
43
0
Order By: Relevance
“…Previous research findings have indicated AVA’s antioxidant and anti-inflammatory properties in both preclinical and human studies [ 18 , 19 , 20 , 21 ]. Zhang et al [ 19 ] and Koenig et al [ 18 ] investigated the effects of chronic AVA supplementation on exercised-induced ROS generation in their clinical studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research findings have indicated AVA’s antioxidant and anti-inflammatory properties in both preclinical and human studies [ 18 , 19 , 20 , 21 ]. Zhang et al [ 19 ] and Koenig et al [ 18 ] investigated the effects of chronic AVA supplementation on exercised-induced ROS generation in their clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research findings have indicated AVA’s antioxidant and anti-inflammatory properties in both preclinical and human studies [ 18 , 19 , 20 , 21 ]. Zhang et al [ 19 ] and Koenig et al [ 18 ] investigated the effects of chronic AVA supplementation on exercised-induced ROS generation in their clinical studies. Koenig et al [ 18 ] demonstrated in their study that participants supplemented with two AVA-enriched cookies daily for eight weeks decreased the ROS generation from the neutrophil respiratory burst (NRB) and plasma C-reactive protein (CRP) levels after a high-intensity training.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations